Barefoot in Fire : A World War II Childhood (Manila, Philippines : Tahanan Books for young readers, 2005)
1. Lewis, Barbara Ann G.-- Childhood and youth. 2. World War II, 1939--1945--Personal narratives. 3. Pollar, Barbara. 4. Barefoot in fire : a World War II childhood.
Basic Ed. Student